Pendampingan Psikologis pada Anak yang Mengalami Trauma Kekerasan Seksual di Sentra Budi Perkasa Palembang - Rizki Amaliyah; Jasmine Aliyyah Putri (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Children are valuable assets of a nation who have the right to protection, proper care, education, and a safe environment to support their optimal growth and development. This community service program implemented a Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) approach to provide psychological assistance for children and adolescents who had experienced trauma, including sexual and physical violence. The results demonstrated that integrating the principles of Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) and Trauma-Informed Care (TIC) effectively supported the psychological recovery of child survivors of sexual violence. The assistance improved emotional regulation, communication skills, social interaction, and participation in daily activities. Furthermore, the program developed a Happiness Recovery framework consisting of six key components: empowerment, self-acceptance, positive emotions, positive activities, social support, and self-worth. This framework may serve as a practical reference for implementing psychological assistance programs for child survivors of sexual violence in rehabilitation institutions.